proposed rules in the eastern musical theories. (Al-Academy, 2016)
This paper deals with one of important topics that serve the art movement music, which is looking at the stairs of Arab music in the process of reaching to the directory musical on the subject of so-called (Photo by stairs music) and that by comparing the method used previously and the proposed rules reached by the researcher and received the patent invention, the method is easier for the musician and the author in a directory of peace Arab music when used on grades and half grades voice, and to achieve its objectives researcher dealt with the problem that is determined by the multitude of stairs leading Arab and the difficulty of keeping its catalog of music, and for being an anchor and pillar of the music was taken up and put her importance and objectives. The theoretical framework Vahtoy on the following topics: (the date of the Arab musical scale - Specifications for the Arab peace signs and conversion in the basic stairs), as research has included some of the signs of transformation in Sub-stairs. The terms of the previous studies did not find a researcher studies similar to this study. The research methodology and procedures have relied on the comparison between the rules used in the past and proposed rules applicable to a number of scores music and fairness in peace and to identify similarities among them and that will help us in the curriculum theories of music, in addition to the fact that this comparison shows the importance of these rules and use them practically and theoretically in Arabic Music , the researcher has quit, achieving the results of its objectives, and develop some recommendations and followed by a list of sources.